Simultaneous parameter and state estimation of shear buildings. (March 2016) - Concha, Antonio; Alvarez-Icaza, Luis; Garrido, Rubén
Abstract: This paper proposes an adaptive observer that simultaneously estimates the damping/mass and stiffness/mass ratios, and the state of a seismically excited building. The adaptive observer uses only acceleration measurements of the ground and floors for both parameter and state estimation; it identifies all the parameter ratios, velocities and displacements of the structure if all the floors are instrumented; and it also estimates the state and the damping/mass and stiffness/mass ratios of a reduced model of the building if only some floors are equipped with accelerometers. This observer does not resort to any particular canonical form and employs the Least Squares (LS) algorithm and a Luenberger state estimator. The LS method is combined with a smooth parameter projection technique that provides only positive estimates, which are employed by the state estimator. Boundedness of the estimate produced by the LS algorithm does not depend on the boundedness of the state estimates. Moreover, the LS method uses a parametrization based on Linear Integral Filters that eliminate offsets in the acceleration measurements in finite time and attenuate high-frequency measurement noise. Experimental results obtained using a reduced-scale five-story confirm the effectiveness of the proposed adaptive observer. Abstract : Highlights: Adaptive observer to recover parameters and state of a shear building model. Convergence parameters and state estimator is decoupled by linear integral filters. Only acceleration measurements are required. Bias in accelerometers is eliminated and noise attenuated. Experimental results on a scaled building are presented.